2010
DOI: 10.1111/j.1476-5381.2010.01059.x
|View full text |Cite
|
Sign up to set email alerts
|

Tolerance to allopregnanolone with focus on the GABA‐A receptor

Abstract: Many studies have suggested a relationship between stress, sex steroids, and negative mental and mood changes in humans. The progesterone metabolite allopregnanolone is a potent endogenous ligand of the g-amino butyric acid -A (GABA-A) receptor, and the most discussed neuroactive steroid. Variations in the levels of neuroactive steroids that influence the activity of the GABA-A receptor cause a vulnerability to mental and emotional pathology. There are physiological conditions in which allopregnanolone product… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
66
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 85 publications
(69 citation statements)
references
References 172 publications
(281 reference statements)
2
66
0
1
Order By: Relevance
“…Data available in the literature indicate that THP treatment as well as its withdrawal (i.e., 24 h) transiently increases the expression of α4 subunit in the hippocampus [60]. A decrease of this GABA-A subunit has been reported after neonatal THP treatment [61] or following the development of acute THP tolerance [62]. Usually, the effect of THP on the expression of α4 subunit is associated with changes in the expression of δ subunit [60], which was not affected in our experimental model.…”
Section: Discussionmentioning
confidence: 99%
“…Data available in the literature indicate that THP treatment as well as its withdrawal (i.e., 24 h) transiently increases the expression of α4 subunit in the hippocampus [60]. A decrease of this GABA-A subunit has been reported after neonatal THP treatment [61] or following the development of acute THP tolerance [62]. Usually, the effect of THP on the expression of α4 subunit is associated with changes in the expression of δ subunit [60], which was not affected in our experimental model.…”
Section: Discussionmentioning
confidence: 99%
“…It is also obvious that depression and anxiety are at least as common during pregnancy as during other time points in a woman's fertile life [41], despite the anxiolytic and sedative levels of allopregnanolone. Given the possibility that a tolerance develops during several months of continuous increase [42], it is reasonable that only women with very high levels, or a steeper increase, would benefit from the protective effects of allopregnanolone during pregnancy. Insensitivity to other substances acting on the GABA A receptor, as well as tolerance to the anticonvulsive, learning-impairing, and anesthetic effects of allopregnanolone exposure have been demonstrated in rodent models [42].…”
Section: Discussionmentioning
confidence: 99%
“…Given the possibility that a tolerance develops during several months of continuous increase [42], it is reasonable that only women with very high levels, or a steeper increase, would benefit from the protective effects of allopregnanolone during pregnancy. Insensitivity to other substances acting on the GABA A receptor, as well as tolerance to the anticonvulsive, learning-impairing, and anesthetic effects of allopregnanolone exposure have been demonstrated in rodent models [42]. The GABA A receptor sensitivity to allopregnanolone may depend on receptor subunit composition, where the relative contributions of subunits α4 and δ have received most attention [43,44].…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have shown that this action is stimulated by EHP, occurring mainly via the GABA A receptor (Turkmen et al, 2011). Following the reasoning above, from the prior knowledge that there is an increase of GABAergic fibers in rats during the first 2 weeks postnatal (Xia and Haddad, 1992).…”
Section: Discussionmentioning
confidence: 99%